2018
DOI: 10.31219/osf.io/yk3n5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of amphetamine exposure during adolescence on behavior and prelimbic cortex neuron activity in adulthood

Abstract: Repeated exposure to psychostimulants during adolescence produces long-lasting changes in behavior that may be mediated by disrupted development of the mesocorticolimbic dopamine system. Here, we tested this hypothesis by assessing the effects of amphetamine (AMPH) and dopamine receptor-selective drugs on behavior and neuron activity in the prelimbic region of the medial prefrontal cortex (PFC). Adolescent male, Sprague-Dawley rats were given saline or 3 mg/kg AMPH between postnatal day (P) 27 and P45. In Expe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…These effects were mediated at least in part by reduced sensitivity of D1 receptors, which is in line with our work demonstrating that D1 receptor expression in the PFC, but not the nucleus accumbens, is reduced for at least 3 weeks following this same AMP exposure during adolescence (Kang et al, 2016b). We also showed that adult rats pre-treated with AMP during adolescence were more sensitive to the behavioral effects of D1 agonists, which is one predicted result of AMP-induced disruptions in D1 receptor expression (Sherrill and Gulley, 2018). However, it is important to note that we have also recently reported no reduction in D1 receptor expression in the PFC following LgA METH self-administration that began during adolescence (P41) or adulthood (P91; .…”
Section: Laboratory Animal Studies Of Consequences On Behavior and Neurobiologysupporting
confidence: 91%
“…These effects were mediated at least in part by reduced sensitivity of D1 receptors, which is in line with our work demonstrating that D1 receptor expression in the PFC, but not the nucleus accumbens, is reduced for at least 3 weeks following this same AMP exposure during adolescence (Kang et al, 2016b). We also showed that adult rats pre-treated with AMP during adolescence were more sensitive to the behavioral effects of D1 agonists, which is one predicted result of AMP-induced disruptions in D1 receptor expression (Sherrill and Gulley, 2018). However, it is important to note that we have also recently reported no reduction in D1 receptor expression in the PFC following LgA METH self-administration that began during adolescence (P41) or adulthood (P91; .…”
Section: Laboratory Animal Studies Of Consequences On Behavior and Neurobiologysupporting
confidence: 91%